Adaptive low computational cost optimisation method for performance-based seismic design of friction dampers. (1st November 2019) - Nabid, Neda; Hajirasouliha, Iman; Petkovski, Mihail
Highlights: A low-cost adaptive optimisation method is developed for performance-based design of friction dampers. Efficiency is significantly improved by modifying convergence factor based on performance violation level. Proposed method leads to optimum answers with up to 300 times lower number of analyses compared to GA. Coupled UDD-GA approach can increases the optimisation speed of GA by up to 3 times. Optimised structures satisfy predefined performance targets under a set of spectrum compatible design earthquakes. Abstract: This study aims to improve the computational efficiency and convergence rate of an already existing optimisation method for friction-based dampers based on the concept of Uniform Distribution of Deformation (UDD) and demonstrate the reliability of the results compared to Heuristic optimisation methods such as GA. In the proposed approach, the computational cost is considerably reduced by using a convergence factor that is modified in proportion to the level of performance violation. To investigate the efficiency of the proposed method, 3, 5 and 10-storey RC frames with friction dampers are optimised using adaptive UDD method, Genetic Algorithm (GA) and a coupled UDD-GA approach. The results indicate that the adaptive UDD method can lead to optimum design solutions with significantly lower computational costs (up to 300 times lower number of non-linear dynamic analyses) compared to both GA and coupled UDD-GA methods. It is shown that frames optimised under a single spectrum-compatible earthquake can efficiently satisfy the predefined performance targets under a set of synthetic earthquakes representing the design spectrum. Therefore, the proposed method should provide a reliable approach for more efficient design of friction-based dampers.